A Study on designing gated residential area based on crime prevention through enviromental design approach (CPTED) in Taman Mutiara Indah, Jitra, Kedah / Muhammad Nazreen Firdaus Mohamad Nizar - Muhammad Nazreen Firdaus, Mohamad Nizar (2020)
In new era, the prevailing housing development trend is gated residential neighbourhood. This trend is been most one of the popular pattern of housing development in Malaysia. This gated residential concept design is to show that neighbourhood build durability around themselves to improve the safety also the defends towards criminal behaviour. From that, this gated residential can provide sense of protection to residents. In residential of Taman Mutiara Indah, there are lack of safety aspects to ensure the safety of residents in high level. This because, all the existing safety features especially fences or wall are not in good condition and have a lot of damage on physical. In other hands, these can decrease the quality of the living for residents. environment is important for an individual’s wellbeing. The factors that contribute to the inhabitants’ satisfaction in a living environment. The issues that being happened at the study area is lack of safety in neighbourhood environment and a part of that safety issues in neighbourhood environment decreases the quality of life for the residents. The aim of the study is to enhance the gated residential neighbourhood of Taman Mutiara Indah based on the Crime Prevention Through Environmental Design (CPTED) approach. The objective is to identify the dimensions of safety issues and environment problems of the study, to analyse the solution of the issues by developing strategies in order to enhance and resolve the current crimes in residential area, to propose the idea of implementation and recommendations based on important findings of the study. The methodology of the proposal report have six stage which are establish the goal and objectives, literature review, data collection, data analysis, findings and recommendation. Lastly, results showed that the recommendations and conclusions for the safety and security at residential area based on CPTED approach. This study recommends an immediate recommendation from the analysis and findings like the foster Crime Prevention Through Environmental Design (CPTED) and other initiatives that when combined can significantly enhance the safety in Taman Mutiara Indah such as improving security system, improving new fences for high level security and new landscaping for residential.